Plastics compounding and polymer processing : fundamentals, machines, equipment, application technology - Kohlgruber, Klemens; Bierdel, Michael; Rust, Harald (Hanser Publications, 2022)
Plastics production comprises the main process steps "synthesis (reaction)", "preparation/compounding" at the raw material manufacturer and compounder, and "processing" (shaping into semi-finished or finished products). In this handbook, the central middle step, preparation and compounding, is discussed. The preparation tasks include the removal of components, the incorporation of additives, and the change of particle size. Compounding is the incorporation of additives into a polymer or plastic. The process engineering fundamentals and the specific equipment and machines used are described. The specialist authors impart their knowledge from the fields of research, polymer production, and equipment/machine production with applications in plastics technology.--